An Assessment of Ore Waste and Dilution Resulting From Buffer/Choke Blasting in Surface Gold Mines - Dale S. Preece; Stephen H. Chung; J Paul Tidman (International Society of Explosives Engineers, 1998)
A discrete element computer program named DMC_BLAST (Distinct Motion Code) has been under development since 1987 for modeling rock blasting (Preece & Taylor, 1989). This program employs explicit time integration and uses spherical or cylindrical elements that are represented as circles in two dimensions (2-D). DMC_BLAST calculations compare favorably with data from actual bench blasts (Preece et al, 1993).